PENGARUH INISIASI MENYUSU DINI TERHADAP KEBERHASILAN ASI EKSKUSIF: THE EFFECT OF EARLY BREASTFEEDING INITIATION ON THE SUCCESS OF EXCLUSIVE BREASTFEEDING - Stianto, Mitayakuna; Fitriana, Alfira; Fatma, Inge Devita; Bachtiar, Ayu Mayhesa Gumilang Rizki (WELL BEING, 2024)
Introduction: Early initiation of breastfeeding (IMD) is the process of breastfeeding the baby immediately after birth, where the baby is allowed to find the mother's nipple alone (not offered the nipple). IMD will greatly assist in the continuation of exclusive breastfeeding. The success factor is also strongly influenced by the attitude, knowledge and motivation of the midwife/doctor of the labor helper. The failure factor in the implementation of IMD is influenced by several factors, among others, the birth mother faces many obstacles to perform IMD on the baby who is born at the place of delivery, the lack of support provided by the family, as well as the number of mothers who have not been equipped with sufficient knowledge about the benefits of IMD implementation. Objective: to determine the effect of early breastfeeding initiation on the success of exclusive breastfeeding. Methods: literature review was conducted based on issues, methodology, similarities and research proposals. Results: Of the 10 studies used, 1 of them used analytic methods and 6 others used cross sectional methods and 3 others used case control. Conclusion: IMD affects the success of exclusive breastfeeding.